PENGARUH ROLE MODEL TERHADAP INTENSI BERWIRAUSAHA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI STKIP PERSADA KHATULISTIWA SINTANG - Maria Teovela; Emilia Dewiwati Pelipa; Dessy Triana Relita; Avelius Dominggus Sore (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study was motivated by the low entrepreneurial intention of students of the Economic Education Study Program of STKIP Persada Khatulistiwa Sintang, even though students have received entrepreneurship education, many students are still afraid to start entrepreneurship and lack role models that inspire students in entrepreneurship. This study aims to determine the Role Model on Entrepreneurial Intention of students of the Economic Education Study Program of STKIP Persada Khatulistiwa Sintang. The method used is a quantitative approach with simple linear regression analysis. The population and sample of the study amounted to 42 students. The results of the analysis show that the t-count value of 4.725> t table of 2.023 with a significance value of 0.000 <0.05, which means that role models have a positive and significant effect on entrepreneurial intention. based on the results of the study it can be concluded that relevant role models are able to encourage students' entrepreneurial intentions to enter the world of entrepreneurship. The results of this study are expected to be a basis for the campus in developing a more inspiring entrepreneurial environment and encouraging the active role of role models around students..